A binary transition metal sulfide composite material, preparation method and application thereof

By preparing binary transition metal sulfide composite materials, the problems of low capacity and poor cycle stability of sodium ion battery negative electrode materials are solved. By forming a multi-stage three-dimensional heterostructure, the stability and capacity of the battery are improved, and sodium ion is achieved. Efficient migration and long life of materials.

CN115377375BInactive Publication Date: 2024-12-31GUANGZHOU UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210669608.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-14
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode materials have low capacity and poor circulation stability, mainly due to volume expansion and shuttle effects.

Method used

Using the preparation method of binary transition metal sulfide composite materials, MnS@ReS2 is prepared under hydrothermal conditions by compounds such as potassium permanganate and dopamine to form a multi-stage three-dimensional heterostructure of nanosheets growing on the surface of nanorods, combined with conductive agents Make a negative electrode material with binder.

Benefits of technology

The contact area between the electrode material and the electrolyte is significantly improved, the mobility of sodium ions is enhanced, the stability and circulation performance of the battery are improved, the volume expansion effect is alleviated, and the high capacity and good circulation stability are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115377375B_ABST
    Figure CN115377375B_ABST
Patent Text Reader

Abstract

The invention discloses a binary transition metal sulfide composite material, a preparation method and an application thereof. The preparation method comprises the following steps: S1: potassium permanganate is dissolved in deionized water, PVP is added, and magnetic stirring is performed for 30 minutes; then the solution obtained in S1 is transferred to a polytetrafluoroethylene hydrothermal kettle for heating for 9 hours, and MnO nanowires are obtained by centrifugation; MnO, tris(hydroxymethyl)aminomethane, and dopamine are dissolved in deionized water, and fully stirred for 7 hours; then the product obtained in S3 is put into a centrifuge for centrifugation to obtain MnO@PDA; MnO@PDA is sulfided for 2 hours to obtain MnS@C; MnS@C, ammonium perrhenate thiourea, and hydroxylamine hydrochloride are dissolved in deionized water; then the product obtained in S6 is heated for 22 hours, and finally centrifuged to obtain MnS@ReS2. The binary transition metal sulfide composite material enlarges the contact area between the electrode material and the electrolyte, and improves the mobility of sodium ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a binary transition metal sulfide composite material, a preparation method and application thereof. Background Art

[0002] Currently, many technical problems have seriously hindered the utilization and development of sodium-ion batteries (SIBs), but sodium-ion batteries are still considered to be the most promising energy storage devices. In order to solve these problems, great efforts have been made to develop anode materials. Anode materials can be divided into intercalation / deintercalation type, conversion type and alloying type according to different reaction mechanisms. The stable intercalation mechanism is limited by low reversible capacity, while the conversion and alloying mechanisms can bring high capacity but are severely affected by large volume changes during charging and discharging. Transition metal sulfides (TMDs) have attracted more attention due to their unique electrochemical properties and energy storage mechanisms;

[0003] Compared with other TMDs, MnS is a promising battery anode material due to its lower redox potential and larger theoretical capacity (616 mAh g -1 ). Rhenium disulfide (ReS 2 ) has unique structure and chemical properties. Its S-Re-S "sandwich" sandwich structure is connected by covalent bonds with weak van der Waals interactions. DFT calculations show that the unit cell energy between S-Re-S layers is only 18MeV, compared with 460MeV of MoS2, which has obvious advantages in promoting the insertion and extraction of sodium ions;

[0004] The current battery negative electrode materials have a low capacity and cannot meet the requirements of today's batteries. During the charge and discharge process, the capacity of metal sulfides decreases due to volume expansion and shuttle effect, and the cycle stability is poor. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a binary transition metal sulfide composite material and its application to solve the problems in the background technology.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a binary transition metal sulfide composite material comprises the following steps:

[0008] S1: 90 mg potassium permanganate (KMnO 4 ) was dissolved in 40 mL of deionized water, and then 50 mg of PVP was added and magnetically stirred for 30 min;

[0009] S2: Then the product obtained in S1 is transferred to a polytetrafluoroethylene hydrothermal reactor and heated at 160°C for 9 hours, followed by centrifugation to obtain MnO nanowires;

[0010] S3: Dissolve 30 mg MnO, 60 mg tris(hydroxymethyl)aminomethane) and 20 mg dopamine in deionized water and stir thoroughly for 7 h;

[0011] S4: Then, the product obtained in S3 is placed in a centrifuge and centrifuged to obtain MnO@PDA;

[0012] S5: MnO@PDA was sulfurized at 500 °C for 2 h in a nitrogen atmosphere to obtain MnS@C;

[0013] S6: Dissolve 30 mg MnS@C, 67 mg ammonium perrhenate, 94 mg thiourea, and 41 mg hydroxylamine hydrochloride in 40 mL deionized water;

[0014] S7: The product obtained in S6 was then transferred to a polytetrafluoroethylene hydrothermal reactor and heated at 210°C for 22 hours, and finally centrifuged to obtain MnS@ReS 2 ;

[0015] S8: The obtained MnS@ReS 2 Perform performance testing. The testing method is as follows:

[0016] 5) MnS@ReS 2 , acetylene black (conductive agent) and sodium alginate (binder) are mixed evenly in a mass ratio of 7:2:1;

[0017] 6): Add appropriate amount of deionized water to make slurry;

[0018] 7): The slurry is evenly applied on copper foil to form a negative electrode, and then a sodium sheet is used as a positive electrode, a 1 mol / L sodium hexafluorophosphate solution (the solvent is dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate in a volume ratio of 1:1) is used as an electrolyte, and glass fiber is used as a separator;

[0019] 8): Finally, assemble into a half-battery and perform charge and discharge tests at different current densities.

[0020] Preferably, the PVP in S1 is an additive for preparing rod-shaped MnO, and PVP can be replaced by CTAB.

[0021] Preferably, the hydrothermal reaction time for preparing rod-shaped MnO in S2 may be 8-10 h.

[0022] Preferably, the hydrothermal reaction temperature for preparing rod-shaped MnO in S2 may be 140-180°C.

[0023] Preferably, the protective atmosphere for the sulfurization of MnO@PDA in S5 can be one of a nitrogen atmosphere, an argon atmosphere, and a helium atmosphere.

[0024] Preferably, the heating rate during the sulfurization of MnO@PDA in S5 is 2-5°C / min.

[0025] Preferably, the stirring time in S3 may be 6-8 hours.

[0026] A binary transition metal sulfide composite material prepared by the above method and its application, the material is applied to the manufacture of negative electrodes for sodium batteries. The material combines multiple metal sulfides, thus having a higher capacity, and the controllable preparation of the morphology can effectively inhibit the volume expansion of the material during the charge and discharge process, alleviate the shuttle effect caused by polysulfides to a certain extent, and obtain better cycle stability.

[0027] The present invention provides a binary transition metal sulfide composite material, a preparation method and an application thereof, which have the following beneficial effects:

[0028] (1) The binary transition metal sulfide composite material expands the contact area between the electrode material and the electrolyte and improves the mobility of sodium ions;

[0029] (2) The binary transition metal sulfide composite material and the synergistic effect of the binary metal sulfide composite are beneficial to the stability of the battery;

[0030] (3) In the binary transition metal sulfide composite material, rhenium disulfide nanosheets grow on the surface of manganese sulfide nanowires to form a multi-level three-dimensional heterogeneous structure, which increases the surface area and makes the electrode material have better performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the MnS@ReS embodiment of the present invention. 2 Schematic diagram of the preparation method;

[0032] Figure 2 MnS@ReS prepared in this embodiment of the present invention 2 SEM images of the composite material;

[0033] Figure 3 MnS@ReS prepared in this embodiment of the present invention 2 The rate cycle curve diagram;

[0034] Figure 4 This is a cycling performance diagram of MnS@ReS prepared in an embodiment of the present invention at a current density of 1.0 A / g. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0036] Examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0037] Example

[0038] See also Figure 1-4 The method for preparing the binary transition metal sulfide composite material provided by the embodiment of the present invention comprises the following steps:

[0039] S1: 90 mg potassium permanganate (KMnO 4 ) was dissolved in 40 mL of deionized water, and then 50 mg of PVP was added and magnetically stirred for 30 min. PVP is an additive in the preparation of rod-shaped MnO, and PVP can be replaced by CTAB;

[0040] S2: Then the product obtained in S1 is transferred to a polytetrafluoroethylene hydrothermal reactor and heated at 160°C for 9 hours, and then centrifuged to obtain MnO nanowires. The hydrothermal reaction time of rod-shaped MnO can be 8-10 hours, and the hydrothermal reaction temperature of rod-shaped MnO can be 140-180°C;

[0041] S3: Dissolve 30 mg MnO, 60 mg tris(hydroxymethyl)aminomethane) and 20 mg dopamine in deionized water and stir thoroughly for 7 h. The stirring time can be 6-8 h.

[0042] S4: Then, the product obtained in S3 is placed in a centrifuge and centrifuged to obtain MnO@PDA;

[0043] S5: sulfurizing MnO@PDA at 500°C for 2h in a nitrogen atmosphere to obtain MnS@C. The protective atmosphere for sulfurizing MnO@PDA can be one of nitrogen atmosphere, argon atmosphere, and helium atmosphere. The heating rate during sulfurizing MnO@PDA is 2-5°C / min.

[0044] S6: Dissolve 30 mg MnS@C, 67 mg ammonium perrhenate, 94 mg thiourea, and 41 mg hydroxylamine hydrochloride in 40 mL deionized water;

[0045] S7: The product obtained in S6 was then transferred to a polytetrafluoroethylene hydrothermal reactor and heated at 210°C for 22 hours, and finally centrifuged to obtain MnS@ReS 2 .

[0046] Furthermore, the following performance testing steps are included:

[0047] S8: The obtained MnS@ReS 2 Perform performance testing. The testing method is as follows:

[0048] 8) MnS@ReS 2 , acetylene black (conductive agent) and sodium alginate (binder) are mixed evenly in a mass ratio of 7:2:1;

[0049] 9): Add appropriate amount of deionized water to make slurry;

[0050] 10): The slurry is evenly applied on a copper foil to form a negative electrode, and then a sodium sheet is used as a positive electrode, a 1 mol / L sodium hexafluorophosphate solution (the solvent is dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate in a volume ratio of 1:1) is used as an electrolyte, and glass fiber is used as a separator;

[0051] 8): Finally, assemble into a half-battery and perform charge and discharge tests at different current densities.

[0052] A binary transition metal sulfide composite material prepared by the above method and its application, the material is applied to the manufacture of negative electrodes for sodium batteries. Since the material combines multiple metal sulfides, it has a higher capacity, and the controllable preparation of the morphology can effectively inhibit the volume expansion of the material during the charge and discharge process, alleviate the shuttle effect caused by polysulfides to a certain extent, and obtain better cycle stability.

[0053] From the attached Figure 2 It can be seen that the prepared binary transition metal sulfide is a nanosheet structure grown on the surface of nanorods;

[0054] From the attached Figure 3 It can be seen that the discharge capacity is 420mAh / g at a current density of 0.1A / g, and the discharge capacity is 200mAh / g at a current density of 5A / g, which illustrates the high specific capacity of the material;

[0055] From the attached Figure 4 It can be seen that the material has a high specific capacity, a high coulombic efficiency in the first cycle, and the subsequent coulombic efficiency basically remains at around 100%. After 400 cycles, it still maintains a specific capacity of 300 mAh / g, indicating that the material structure is stable.

[0056] The binary transition metal sulfide composite material is prepared by mixing 90 mg potassium permanganate (KMnO 4) was dissolved in 40 mL of deionized water, and then 50 mg of PVP was added and magnetically stirred for 30 min; then the product obtained in S1 was transferred to a polytetrafluoroethylene hydrothermal reactor and heated at 160 ° C for 9 h, and centrifuged to obtain MnO nanowires; 30 mg of MnO, 60 mg of trishydroxymethylaminomethane, and 20 mg of dopamine were dissolved in deionized water and stirred for 7 h; then the product obtained in S3 was centrifuged to obtain MnO@PDA; MnO@PDA was sulfurized at 500 ° C for 2 h in a nitrogen atmosphere to obtain MnS@C; 30 mg of MnS@C, 67 mg of ammonium perrhenate, 94 mg of thiourea, and 41 mg of hydroxylamine hydrochloride were dissolved in 40 mL of deionized water; then the product obtained in S6 was transferred to a polytetrafluoroethylene hydrothermal reactor and heated at 210 ° C for 22 h, and finally centrifuged to obtain MnS@ReS 2 ; The obtained MnS@ReS 2 The performance test was carried out as follows: MnS@ReS 2 , acetylene black (conductive agent), and sodium alginate (binder) are evenly mixed in a mass ratio of 7:2:1; then an appropriate amount of deionized water is added to form a slurry; the slurry is evenly applied on a copper foil to form a negative electrode, and then a sodium sheet is used as a positive electrode, a 1 mol / L sodium hexafluorophosphate solution (the solvent is dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate in a volume ratio of 1:1) is used as an electrolyte, and glass fiber is used as a separator.

[0057] The binary transition metal sulfide composite material, preparation method and application thereof provided by the above embodiments of the present invention expand the contact area between the electrode material and the electrolyte and improve the mobility of sodium ions.

[0058] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprising a reference structure" do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0059] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0060] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a binary transition metal sulfide composite material, characterized in that: It includes the following steps: S1: Dissolve 90 mg potassium permanganate (KMnO4) in 40 mL deionized water, add 50 mg PVP, and stir magnetically for 30 min; S2: Then the product obtained in S1 is transferred to a polytetrafluoroethylene hydrothermal reactor and heated at 160°C for 9 hours, followed by centrifugation to obtain MnO nanowires; S3: Dissolve 30 mg MnO, 60 mg tris(hydroxymethyl)aminomethane) and 20 mg dopamine in deionized water and stir thoroughly for 7 h; S4: Then, the product obtained in S3 is placed in a centrifuge and centrifuged to obtain MnO@PDA; S5: MnO@PDA was sulfurized at 500 °C for 2 h in a nitrogen atmosphere to obtain MnS@C; S6: Dissolve 30 mg MnS@C, 67 mg ammonium perrhenate, 94 mg thiourea, and 41 mg hydroxylamine hydrochloride in 40 mL deionized water; S7: The product obtained in S6 is then transferred to a polytetrafluoroethylene hydrothermal autoclave and heated at 210°C for 22 hours. Finally, it is placed in a centrifuge and centrifuged to obtain MnS@ReS2.

2. The method for preparing the binary transition metal sulfide composite material according to claim 1, characterized in that: It also includes the following steps: S8: The obtained MnS@ReS2 is subjected to a performance test, and the test method is as follows: 1): Mix MnS@ReS2, conductive agent acetylene black and binder sodium alginate in a mass ratio of 7:2:1; 2): Add appropriate amount of deionized water to make slurry; 3): The slurry is evenly applied on a copper foil to form a negative electrode, and then a sodium sheet is used as a positive electrode, a sodium hexafluorophosphate solution with a concentration of 1 mol / L is used as an electrolyte, and a glass fiber is used as a separator; the solvent of the sodium hexafluorophosphate solution is dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate in a volume ratio of 1:1; 4): Finally, assemble into a half-battery and perform charge and discharge tests at different current densities.

3. The method for preparing the binary transition metal sulfide composite material according to claim 1, characterized in that: The PVP in step S1 is an additive for preparing rod-shaped MnO, and the PVP is replaced by CTAB.

4. The method for preparing the binary transition metal sulfide composite material according to claim 1, characterized in that: The hydrothermal reaction time for preparing rod-shaped MnO in step S2 is 8-10 hours.

5. The method for preparing the binary transition metal sulfide composite material according to claim 1, characterized in that: The hydrothermal reaction temperature for preparing rod-shaped MnO in step S2 is 140-180°C.

6. The method for preparing the binary transition metal sulfide composite material according to claim 1, characterized in that: The protective atmosphere for sulfurization of MnO@PDA in step S5 is one of nitrogen atmosphere, argon atmosphere and helium atmosphere.

7. The method for preparing the binary transition metal sulfide composite material according to claim 1, characterized in that: The heating rate during the sulfurization of MnO@PDA in step S5 is 2-5°C / min.

8. The method for preparing the binary transition metal sulfide composite material according to claim 1, characterized in that: The stirring time in step S3 is 6-8h.

9. A binary transition metal sulfide composite material prepared by the method according to any one of claims 1 to 7.

10. An application of the binary transition metal sulfide composite material according to claim 9, characterized in that: The binary transition metal sulfide composite material is applied to the manufacture of the negative electrode of the sodium battery.